Perhitungan Harga Pokok Produksi Menggunakan Metode Full Costing Untuk Menentukan Harga Jual Pada CV Kepercayaan Bersama - Adelia, Mutiara Shafa; Apriliawati, Yeti (Indonesian Accounting Research Journal, 2025)
CV Kepercayaan Bersama is a business engaged in the production of t-shirts located on Jl. Otto Iskandar Dinata No. 258, Nyengseret, Kec. Astanaanyar, Bandung City, West Java 40242. This research was conducted to determine the calculation of the cost of production by company and according to the full costing method, as well as to determine the selling price. This study uses a descriptive analysis method with data collection techniques using interviews and documentation. This research was conducted with a sample of t-shirt production in March 2023. The results of this study show that there is a difference in factory overhead costs, where the cost of production using the full costing method is greater than the company's calculations. This happens because the company does not include factory overhead costs as a whole. Thus, it will affect the selling price of the product. The result of calculating the cost of production according to the company is IDR106,500. with a selling price of IDR139,000, while the calculation uses the full costing method is IDR112,509 with a selling price of IDR146,500.